2022
DOI: 10.1101/2022.12.09.519591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

METTL3 drives telomere targeting of TERRA lncRNA through m6A-dependent R-loop formation: a therapeutic target for ALT-positive neuroblastoma

Abstract: Telomerase-negative tumors can maintain telomere length by alternative lengthening of telomeres (ALT) but the mechanism behind ALT is poorly understood. Aggressive Neuroblastoma (NB), in particular, relapsed tumors are positive for ALT (ALT+) which suggests that better dissection of the ALT mechanism could provide novel therapeutic opportunities. TERRA long non-coding RNA (lncRNA) which is derived from the telomere ends is localized to telomeres in R-loop dependent manner and is essential for telomere maintena… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 87 publications
(174 reference statements)
2
7
0
Order By: Relevance
“…Recently, it was shown that telomeric repeat-containing RNA (TERRA), which is transcribed from telomeres and functions in telomere maintenance through R-loop formation, is m6A-modified in a METTL3-depndent manner (11, 49). Considering that ZBTB48 regulates telomere metabolism (40, 41), we examined whether ZBTB48 modulates TERRA m6A in an FTO-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that telomeric repeat-containing RNA (TERRA), which is transcribed from telomeres and functions in telomere maintenance through R-loop formation, is m6A-modified in a METTL3-depndent manner (11, 49). Considering that ZBTB48 regulates telomere metabolism (40, 41), we examined whether ZBTB48 modulates TERRA m6A in an FTO-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we characterized the pattern of m 6 A modifications in hESC and tNCC using m 6 A RIP-seq (19). We observed that consistent with the upregulation of METTL3/14, a higher number of m 6 A peaks was seen in tNCC compared to hESC ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human embryonic stem cell line WA09 (H9) obtained from Dr. Fredrik H. Sterky (Sahlgrenska University Hospital, Gothenburg, Sweden) were cultured on Matrigel-coated plates with iPS-Brew XF (Miltenyi) media. To differentiate hESC to trunk neural crest cells (tNCC), hESC were dissociated using Accutase and seeded (day 0) on Matrigel-coated plates to induce differentiation to neuromesodermal progenitor cells (NMP, day 3) which were then driven to tNCC (days 7-9), sympathoadrenal progenitors (SAP, day 12), and further towards sympathetic neurons (SN, day [19][20][21][22][23][24][25] as described previously (15,16). For neural crest stem cells (NCSC) induction, hESCs were dissociated using Accutase and seeded (day 0) on Matrigel-coated plates at a density of 2x10 4 cells/cm 2 in iPS-Brew XF media with ROCK inhibitor (Y-27632 10 μM).…”
Section: Hesc Culture and Differentiationmentioning
confidence: 99%
See 2 more Smart Citations